Fetal Tetra-Amelia Birth: A Case Report - Eyob Asefa Belay; Anberbir Girma Asebot; Bezza Kedida Dabi (Case Reports in Obstetrics and Gynecology)
Fetal limb anomaly presentation varies greatly. It can present as amelia (complete absence of skeletal part of one or more limb), meromelia (partial absence of skeletal part of one or more limb), phocomelia (only rudimentary limb formed), and minor limb disorders like polydactyly. The complete absence of the four fetal limbs is extremely rare. Incidence of tetra-amelia is not well known, but it is mentioned to be 1–4 in 100,000 births in different literature. Etiopathogenesis of fetal tetra-amelia remains speculative. Tetra-amelia occurs either as tetra-amelia syndrome (when other organ systems are affected too) or isolated tetra-amelia. Tetra-amelia syndrome is more common than isolated tetra-amelia. It occurs secondary to genetic aberration or is sporadic. Genetic inheritance of tetra-amelia may present as autosomal dominance, autosomal recessive, or X-linked recessive. The protein coded on WTN 3 on chromosome 17q21 is important for fetal limb and other organ system formation. Mutation associated with the WTN 3 gene is a known cause for fetal limb malformation. Maternal diabetes, amniotic band syndrome, TORCH (toxoplasmosis, rubella cytomegalovirus, herpes simplex, and HIV) infection, alcohol consumption, and intrauterine exposure to some drugs like thalidomide, glucocorticoids, and sedatives are risk factors for limb malformation. Tetra-amelia can be diagnosed as early as the first trimester of pregnancy. Ultrasound imaging is a gold standard investigation to detect tetra-amelia. Tetra-amelia syndrome is associated with high mortality and morbidity than isolated tetra-amelia. In this case report, we present an extremely rare case, isolated tetra-amelia, born to G3P2 (Gravida 3, Para 2) mother at 36 weeks of gestation. It was diagnosed late in pregnancy at 34 weeks. The fetal organs (kidney, lung, abdominal wall, heart, vertebrae, and brain) were evaluated with ultrasound and were found healthy. She gave birth by cesarean section at 36 weeks of gestation for other obstetric indication. Isolated tetra-amelia is an extremely rare case. Early antenatal ultrasound fetal evaluation should be promoted. Early detection of tetra-amelia helps to provide parental counselling and option of management timely. Parental counselling should involve how to care for the neonate with tetra-amelia. Community awareness creation is important to decrease social stigma against babies with tetra-amelia. In such rare cases, it is important to alert public health researchers for possible further epidemiological study.